Erratum - Todd Levine (Dove Medical Press, 2012)
Levine T. Treating refractory dermatomyositis or polymyositis with adrenocorticotropic hormone gel: a retrospective case series. Drug Des Devel Ther. 2012;6:133–139. The journal should have included the submitted complete disclosure statement in the published article. The correct text is as follows:AcknowledgmentsThe author would like to thank Lynanne McGuire, PhD, of MedVal Scientific Information Services, LLC, for providing medical writing and editorial assistance. This manuscript was prepared according to the International Society for Medical Publication Professionals’ Good Publication Practice for Communicating Company-Sponsored Medical Research: The GPP2 Guidelines.DisclosureDr Levine is a consultant for Questcor Pharmaceuticals, Inc. Funding to support the preparation of this manuscript was provided by Questcor Pharmaceuticals, Inc.Read the original article.